Jakim językiem XVI-wieczni pisarze reformacyjni pisali o wychowaniu dzieci (Gliczner, Kwiatkowski, Lorichius)? - Woźniak, Ewa; Gozdek, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The article is devoted to stylistic properties of three pedagogical works that were published in Protestant circles in the 16th century Poland. The first one is the translation from Latin of the treatise written by German Protestant theologian Reinhard Lorichius titled Księgi o wychowaniu i o ćwiczeniu każdego przełożonego (1558), the second one is the Polish publication of Erazm Gliczner’s Książki o wychowaniu dzieci bardzo dobre, pożyteczne i potrzebne (1558) and the third one is the treatise written by the Italian humanist from the 14th and 15th century titled Książeczki rozkoszne a wielmi użyteczne o poćciwym wychowaniu […] dziatek (1564), translated by Marcin Kwiatkowski. The authors of the analysis recognised didacticism, vividness and erudition as the predominant stylistic features of discussed works. They proved that the 16th century books on upbringing of children had been addressed to readers of every denomination and lacked elements of religious polemics on the linguistic and stylistic level. The ideas of the Reformation can be connected mainly with popularization of the Bible, which was used as the source of exempla and sententiae in the works by Lorichius and Gliczner.